Indoor allergen levels in settled airborne dust are higher in day‐care centers than at home. Issue 6 (15th December 2017) - Sander, I.; Lotz, A.; Neumann, H. D.; Czibor, C.; Flagge, A.; Zahradnik, E.; Raulf, M.
Abstract: Background: Early‐life sensitization to indoor allergens predicts asthma development. The aim of this study was to compare allergen concentrations in day‐care centers (DCC) with those in private homes. Methods: Settled airborne dust was collected 4 times a year from 20 German DCC (620 samples) and from the homes of children and day‐care workers (602 samples) using electrostatic dust collectors (EDC). The samples were analyzed with fluorescence enzyme immunoassays recognizing domestic mite allergens (DM), Fel d 1, Can f 1, and Mus m 1. Pet allergen thresholds that discriminate samples from homes with cats or dogs from those without were calculated using receiver‐operating characteristics. Influences on allergen levels were analyzed using multilevel models. Results: Allergen loads were on average higher in DCC than in homes. In DCC, 96% of the samples were positive for DM, 95% for Can f 1, 90% for Fel d 1, and 83% for Mus m 1. In homes, 84% contained DM, 48.5% Can f 1, 33% Fel d 1, and 43% Mus m 1. The threshold level for homes with dogs was 75 ng/m² Can f 1 (96.8% sensitivity, 96% specificity), and the threshold level for homes with cats was 46 ng/m² Fel d 1 (92% sensitivity, 94.9% specificity). In DCC, Can f 1 and Fel d 1 loads were higher than these thresholds in 37% and 54% of the samples, respectively. Allergen levels were significantly influenced by the season and room type; however, carpets on floors had no influence. Conclusions: Mite, mouse, cat, and dog allergens were mostly higher in DCC than in homes. Exposure to dog and cat allergens in DCC often reached levels of households with pets.